미국 농정의 주요이슈 및 정책결정 주체 - 이현옥 (한국농촌경제연구원, 2008)
This report provides a comprehensive description of the process of agricultural policymaking in the United States. The report describes institutional arrangements involved in the enactment and execution of the policy as well as the basic structure of current agricultural policy. Chapter 1 reviews of current policy issues. Many issues drive the policy agenda of the United States. The review of current policy issues leads the discussion with the 2008 Farm Bill, and then extends to international trade and to specific policy areas. Chapter 2 describes the policy process to deal with the issues reviewed in Chapter 1. The second chapter highlights the institutional arrangements and framework that are involved in policymaking. The relevant government/non-government organizations are introduced and their involvement is described. Much of discussion here is devoted to the nation's legislative branch, Congress, and then extends to executive branches and non-government groups. Chapter 3 explores institutional details about the U.S. Department of Agriculture (USDA), which is the lead agency for policy formulation and implementation. In addition to USDA's role in pre-policy discussion and the formation of policy proposals, USDA implements and executes agricultural policies. In this chapter, we present in detail how the USDA is organized to execute various policies and how the department has been restructured from the historical viewpoint in respond to changing policy focuses. Finally, Chapter 4 describes how many agencies are involved in agricultural policymaking execution. Many farm policies involve institutional frames beyond USDA. It is typical that farm policies involve multi agencies across departments or other independent agencies in their formulation or execution process. In this final chapter, we describe how the policies that are prominent in agriculture, but contain crossover issues such as energy, food safety, air and water, involve other agencies in the policy execution process. This chapter provides useful examples of cross-agency interactions. In this report, coverage under each topic is not, of course, exhaustive. Our modest goal is to provide guidance through this report for those who are interested in the institutional aspect of agricultural policy making in the United States.